Long-term results of minimally invasive stand-alone bi-atrial surgical ablation with a bipolar ablation device for persistent and longstanding persistent AF: a single-center case series of 91 patients. Issue 1 (December 2016) - Janusauskas, Vilius; Puodziukaite, Lina; Maneikiene, Vyte; Zuoziene, Gitana; Radauskaite, Greta; Burneikaite, Greta; Samalavicius, Robertas; Aidietiene, Sigita; Rucinskas, Kestutis; Aidietis, Audrius
Abstract Background Minimally invasive surgical treatment of lone atrial fibrillation (AF) is an alternative for AF that is refractory to medical treatment. We present long-term results of standalone surgical ablation of AF using a bipolar ablation device in 91 consecutive patients. Methods This was an observational, retrospective study of 91 patients (77 % males; mean age, 53 ± 10 years [range, 23–75 years]) who underwent minimally invasive standalone surgical ablation of persistent and longstanding persistent AF using a bipolar ablation device from 2008 to 2014. Mean follow-up was 60 ± 21 months. The absence of arrhythmia was confirmed at 3, 6, and 12 months, and annually thereafter, with 24-hour Holter monitoring. Results The mean duration of preoperative AF was 6.5 ± 5.4 years. Persistent AF was present in 86 % of patients and longstanding persistent AF in 14 %. Mean left atrial diameter was 4.3 ± 0.8 cm. There were two postoperative strokes (2 %) and three conversions to median sternotomy (3 %). Permanent pacemakers were implanted in six (7 %) patients. There were no intra- or postoperative deaths. At 1, 2, 3, 4, and 5 years postoperatively, freedom from AF was 59, 45, 41, 38, and 38 % of patients, respectively. The failure to achieve pulmonary vein isolation was the only independent predictor of long-term recurrence of AF (HR −3 [95 % CI 1, 858 to 8, 586], p  = 0, 001). There was a tendency towards higher rates of SR at long term follow up in patients with pulmonary vein isolation if division of ligament of Marshall was performed (HR - 2 [95 % CI 0.987 to 4, 202], p  = 0, 067). Conclusions In the present series, the efficacy of epicardial surgical ablation was similar to that reported previously. The rate of arrhythmia recurrence increased over time. Achieving pulmonary vein isolation is essential to AF elimination. The division of ligament of Marshall could contribute to improved rates of SR restoration in patients with persistent or long-standing persistent AF if PVI is achieved.